Are Home Owners Really More Unemployed? - Jakob Roland Munch; Michael Rosholm; Michael Svarer (Institute for the Study of Labor (IZA), 2003)
This paper investigates the effects of home-ownership on labour mobility and unemployment duration. We distinguish between finding employment locally or by being geographically mobile. We find that home ownership hampers the propensity to move for job reasons but improves the chances of finding local jobs, which is in accordance with the predictions from our theoretical model. The overall hazard rate into employment is higher for home owners, such that there is a negative correlation between home-ownership and unemployment duration. Our empirical findings thus lend some support for the main mechanism behind the so-called Oswald hypothesis, even if it does not find positive correlation between unemployment duration and home ownership at the individual level.
Keywords: R23; J64; J61; C41; 330; home ownership; labour mobility; unemployment duration; Grundbesitz; Arbeitsmobilität; Arbeitslosigkeit; Dauer; Schätzung; Dänemark